3x-6=9-2x

Simple and best practice solution for 3x-6=9-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6=9-2x equation:


Simplifying
3x + -6 = 9 + -2x

Reorder the terms:
-6 + 3x = 9 + -2x

Solving
-6 + 3x = 9 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-6 + 3x + 2x = 9 + -2x + 2x

Combine like terms: 3x + 2x = 5x
-6 + 5x = 9 + -2x + 2x

Combine like terms: -2x + 2x = 0
-6 + 5x = 9 + 0
-6 + 5x = 9

Add '6' to each side of the equation.
-6 + 6 + 5x = 9 + 6

Combine like terms: -6 + 6 = 0
0 + 5x = 9 + 6
5x = 9 + 6

Combine like terms: 9 + 6 = 15
5x = 15

Divide each side by '5'.
x = 3

Simplifying
x = 3

See similar equations:

| 5[-5a+3(ab+5)]-3ab+5(-4ab+3a+2)= | | 3(-5pq+4p-3)-8pq+2[5p+2(-2pq-1)]= | | 4x7+4-14/2 | | 3[2(-5q+2p)+3q]= | | 27750.00+200.00=125.00(2.50x) | | -3[(-3)(4q+5p)+(-5q)]= | | -[4(-q-4p)-3q]= | | 27750+200x=125(2.50x) | | 5x^4+3x^2=0 | | m-7m-5m+6= | | 2x^2+3x+1=120 | | 125(2.50x)=50000 | | 2x+18=42 | | 8+7h^2= | | 319-114=x | | 1453-323= | | 245-x=128 | | 5x+9-8x=6x-4+2x | | 4X^2+6X=3 | | 4-6x=6x-20 | | x+735=1012 | | 11n-6=9n | | Y^2-12a+35=0 | | f=8*g*h | | 2x^2=9x+18 | | 3120=26000*0.06*t | | x/5-1=x/4 | | 29=5+13+c | | -2(u-7)=3u-11 | | n+6=24 | | 30X^2=54X | | 10x+30=20-11x |

Equations solver categories